Mischief: supporting remote teaching in developing regions - Moraveji, Neema; Kim, Taemie; Ge, James; Pawar, Udai Singh; Inkpen, Kori; Mulcahy, Kathleen (International conference on Human factors in computing systems (CHI 2008), 2008)
Mischief is a system to support traditional classroom practices between a remote instructor and a group of collocated students. Meant for developing regions, each student in the classroom is given a mouse and these are connected to a single machine and shared display. We present observations of teaching practices in rural Chinese classrooms that led to Mischief’s design. Mischief’s user interface, with which scores of collocated students can interact simultaneously, supports anonymous responses, communicates focus of attention, and maintains the role of the instructor. Mischief is an extensible platform in which Microsoft PowerPoint slides, used commonly in developing regions, are made interactive. We setup a controlled environment where Mischief was used by classrooms of children with a remote math instructor. The results from the study provided insight into the usability and capacity of the system to support traditional classroom interactions. These observations were also the impetus for a redesign of several components of Mischief and are also presented. These findings contribute both a novel system for synchronous distance education in an affordable manner and design insights for creators of related systems.